Participation in change, job characteristics, and hedonic well‐being of senior public managers: The moderation effect of change information. Issue 4 (13th May 2020) - Teo, Stephen T. T.; Nguyen, Diep; Shafaei, Azadeh; Pick, David
Abstract: This study contributes to Hobfoll's Conservation of Resources theory by testing a moderated mediation model of the relationship between participation in change and senior managers' hedonic well‐being. Using data collected from 266 Australian senior managers employed in the Commonwealth and State public sector, we tested the interaction of participation in change and change information with job satisfaction, an example of hedonic well‐being at work. Findings from the path analysis produced two new insights. First, both participation in change and information about change are key resources that senior managers can deploy to protect and enhance their job satisfaction. Second, information about change has a buffering effect on the indirect relationship between participation in change and job satisfaction through job control. These two findings have practical implications indicating that it is important to train and equip senior managers in the adoption of effective strategies to acquire job resources in assisting them deal with change induced job demands. Abstract : This study examines the job satisfaction (also known as hedonic well‐being) of Australian senior managers during organisational change. We identified several job related resources which are critical during change.